Search for narrow tt resonances in pp collisions at square root of (s)=1.8 TeV. - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alton, A; Alves, G; et al. (2004)
A search for narrow resonances that decay into tt pairs has been performed using 130 pb(-1) of data in the lepton + jets channel collected by the Dphi detector in pp collisions at square root of (s)=1.8 TeV. There is no significant deviation observed from the standard-model predictions at a top-quark mass of 175 GeV/c2. We therefore present upper limits at the 95% confidence level on the product of the production cross section and branching fraction to tt for narrow resonances as a function of the resonance mass MX. These limits are used to exclude the existence of a leptophobic top-color particle with mass MX<560 GeV/c2, using a theoretical cross section for a width GammaX=0.012MX.